ANALISIS KESENJANGAN KUALITAS PELAYANAN JASA KEAGENAN KAPAL DALAM MENENTUKAN TINGKAT KEPUASAAN PELAYANAN DI PT MAUMERE BAHARI EXPRESS - Jian Richard Mylano; Imanuel Wellem; Nunsio Handrian Meylano; Richardus Muga (Universitas Nusa Nipa Maumere, 2026)
This final report aimed to analyze the service quality gap in ship agency services in determining customer satisfaction levels at PT Maumere Bahari Express. The study was conducted as part of the Merdeka Belajar Kampus Merdeka (MBKM) internship program using a qualitative descriptive approach. Data were collected through interviews with management, employees, and service users (ship crew), direct observation of service processes, and company document review. The analysis was carried out based on the service quality gap model, which includes gaps between customer expectations and management perceptions, management perceptions and service quality specifications, service specifications and service delivery, service delivery and external communication, as well as the gap between expected service and service received by customers.. The results showed that several service gaps still existed in the services, particularly related to administrative speed, clarity of information, service operational standards, as well internal coordination and communication. These gaps affected the level of customer satisfaction, which had not yet been optimal. Therefore, PT Maumere Bahari Express needed to make improvements through strengthening management commitment to service quality, refining standard operating procedures, and enhancini internal and external communication systems in order to improve customer satisfaction sustainably..